A Survey of Mycotoxin Contamination in Fermented Condiments and the Biological Methods for Its Reduction - WANG Lihui, FU Jinhui, LI Chaowei, ZHANG Li, XIA Xiaolong, LI Sitong, ZHANG Mengmei, CHEN Yinzhu, LIU Shuliang, HU Kaidi, ZHAO Ning, LI Qin, LI Jianlong (Shipin Kexue)
The types and pollution status of mycotoxins in different fermented condiments vary both domestically and internationally, which can be attributed to the disparities in raw materials, geographical locations, seasons, and other factors. Microorganisms can convert mycotoxins into low-toxicity or non-toxic substances through the adsorption of cell walls or enzymatic catalysis, thus ensuring the safety of fermented condiments for consumption. With the deepening of research on mycotoxin decontamination, many efficient strains for degrading mycotoxins have been selected. However, there is a relative dearth of studies focusing on safe mycotoxin-degrading microbes isolated from foods. This article summarizes the current status of mycotoxin contamination in fermented condiments, with a focus on mycotoxin-degrading strains from different sources and mycotoxin-degrading enzymes in microbial cells in order to offer insights for reducing harmful fungi and mycotoxin contamination in fermentation condiments.